Factors that effect pay level satisfaction among non-executive in SWM Environment Sdn Bhd / Farah Idayu Khairul Anuar and Saiful Bahari Jasman - Khairul Anuar, Farah Idayu; Jasman, Saiful Bahari (Faculty of Business and Management, 2014)
Compensation plans is very important because that are the tool that unites employers and employees together in one of the most important exchange processes that happens in organizations. Therefore it is important for organizations to enhance employee pay satisfaction because it can enhance productivity and commitment to the organization. This study focuses and examines the factors that affecting the pay satisfaction among non-executives employee in waste management industry. The factors that have been recognized to have an impact to employee’s fairness perception and pay satisfaction are their perception on individual equity, internal equity and external equity. Questionnaires were collected from 80 full time SWM Environment Sdn Bhd employees. The Pearson correlation table shows that only internal equity and external equity has a significant relation towards pay satisfaction whereas internal equity has the most influential factor on determining pay satisfaction. It is hopeful that this research effort will be very useful to the organizations when they want to efficiently and effectively strategically formulating compensation plans that are effective to improve their employee’s performance.